1991
DOI: 10.1097/00000658-199112000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Resection Versus Peritoneal Lavage in Acute Necrotizing Pancreatitis

Abstract: Twenty-one patients with acute fulminant alcoholic pancreatitis were randomly allocated to either pancreatic resection group (11 patients) or nonoperative peritoneal lavage group (10 patients). Only patients under 50 years were included in the study to minimize the role of other severe disease. These patients represented the most severe cases of acute pancreatitis at our Department, constituting only 2% of all patients with acute pancreatitis during this period. The diagnosis was based on clinical symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 7 publications
1
26
0
1
Order By: Relevance
“…l At the beginning of the 1970s, Ranson and colleagues found a mortality of 100% when a patient demonstrated 7 or more of their 11 prognostic signs during the initial 48 h.19'22 Today, a mortality of about 15% is reported in most studies of severe acute pancreatitis. [23][24][25] In the present study, with a median Ranson score of 4.1, the mortality was 16.6%. Death is caused by the failure of different organ systems.…”
Section: Discussionsupporting
confidence: 40%
“…l At the beginning of the 1970s, Ranson and colleagues found a mortality of 100% when a patient demonstrated 7 or more of their 11 prognostic signs during the initial 48 h.19'22 Today, a mortality of about 15% is reported in most studies of severe acute pancreatitis. [23][24][25] In the present study, with a median Ranson score of 4.1, the mortality was 16.6%. Death is caused by the failure of different organ systems.…”
Section: Discussionsupporting
confidence: 40%
“…Eight randomized prospective clinical trials evaluating the influence of continuous peritoneal lavage in patients with acute pancreatitis were performed, but led to divergent results [38,39,40,41,42,43,44,45]. A meta-analysis, however, showed that this therapeutic procedure was not associated with any improvement in mortality or morbidity [46].…”
Section: Principle Of Minimizing Toxicitymentioning
confidence: 99%
“…In those patients surgical measures might not overcome MODS either. These cases may be called 'fulminant acute pancreatitis' and, fortunately, they are rarely seen and represent less than 2% of all patients with SAP [85] . In a report from a tertiary referral centre three out of four patients who died early (i.e.…”
Section: Indications For Surgery and Timing Of The Interventionmentioning
confidence: 99%